Development of decree 1072 of 2015, as a regulatory factor of practices in the construction field for the prevention of workplace accidents with MHF Construark SAS, carried out during the year 2020 in Bogotá - Tabares Barrera, Daniel Augusto; Fuentes Rojas, Ever Angel (Ingeniería Solidaria, 2021)
Introduction: This article "Development of the decree 1072 of 2015, as a regulatory factor of practices in the construction field for the prevention of workplace accidents in MHF Construark SAS" company was executed during 2020 in Bogotá.Background: There has been recurring practices in the construction sector that generate difficulties in the implementation of the SGSST, which may be the main cause of this insufficient implementation, which can lead to workplace accidents and occupational diseases.Objective: The objective of the investigation is to establish the level of compliance in the implementation of the SGSST, in order to identify determining factors that negatively affect such a process.Methods: This research has designed a study with mainly, a qualitative approach. Interviews were conducted with company representatives from the administrative area in charge of implementing the SGSST.Results: The MHF Company has achieved an implementation level of 85%. It is at a high level.Conclusion: This project contributes to the research in terms of the study of SGSST in particular, from a perspective that inquiries factors related to the role of key factors such as senior management and construction personnel.Originality: A small business of the construction field is investigated, setting up human factors in the SGSST implementation processes and the improvement strategyLimitations: information gathering on site was affected due to the circumstances generated by the COVID-19 emergency due to the fact the construction field was forced to suspend work as consequence of the pandemic